2019
DOI: 10.3390/w12010010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Constructed Wetlands’ Potential for the Removal of Cyanobacteria and Microcystins (MC-LR)

Abstract: Microcystis blooms and the subsequent release of hepatotoxic microcystins (MCs) pose a serious threat to the safety of water for human and livestock consumption, agriculture irrigation, and aquaculture worldwide. Microcystin-LR (MC-LR), the most toxic variant of MCs, has been widely detected in a variety of environments such as water, sediments, plants, and many aquatic organisms. Conventional solutions of water treatment are costly, requiring specific infrastructure, as well as specialized personnel and equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…MC extraction from plant samples was conducted as described by Bavithra et al (2020) [ 47 ]. Freeze-dried roots and shoots were ground into fine powder in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…MC extraction from plant samples was conducted as described by Bavithra et al (2020) [ 47 ]. Freeze-dried roots and shoots were ground into fine powder in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Among the MCs, the most toxic is MC-LR [57]. Although slow sand filtration [58] and CW technologies [59] have shown good performance for MC-LR treatment, more studies are required for large-scale applications of slow sand filtration. In addition, CWs require large land areas.…”
Section: Microcystinsmentioning
confidence: 99%
“…Eco-technological purification systems for the removal of cyanobacterial contaminants include constructed wetlands (CWs) using various types of plants [165][166][167], depending on whether these plants have purifying effects on the cyanotoxins in question or household slow sand filters [165][166][167]. For instance, a study with CWs [167] found MC-LR reductions from 5.55 g L −1 to less than 0.1 g L −1 , as well as a 2.39 log 10 unit reduction in Microcystis aeruginosa, while Bavithra et al [165] showed 94-99% cyanobacteria and microcystins (MC-LR) removal from lake water in CWmicrocosms. Moreover, in these eco-technologies, some propose the development of biofilm-based reactors by recycling reverse osmosis (RO) membranes used in desalination plants that have reached the end of their working life.…”
Section: Some Eco-technologies For the Elimination Of Cyanobacterial ...mentioning
confidence: 99%
“…For example, studies have shown that clays such as montmorillonite, kaolinite, smectite, and illite interact electrostatically with MCs due to their chemical composition, allowing adsorption and trapping of these molecules on the surface of clay particles. Similarly, incorporating porous materials [165] such as zeolite, pumice, or pozzolan plays a crucial role in the simultaneous removal of cyanobacteria and cyanotoxins, especially when these materials have considerable porosity in the form of meso-and macropores [102,159].…”
Section: Multi-soil-layering (Msl) Technologymentioning
confidence: 99%